2009
DOI: 10.1088/1742-6596/150/5/052217
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic formation of metastable intermediate state patterns in type-I superconductors

Abstract: Structure of the intermediate state in type-I superconducting lead (Pb) is shown to be very sensitive to the ramp rate of an applied magnetic field. The configurations of resulting static patterns depend sensitively on the shape of the specimen. In particular, geometric barrier, present in the samples with rectangular cross-section, plays an important role in determining the sharp boundary between the phases of different topology. We propose that seemingly laminar (stripe) pattern obtained as a result of the f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…This permits to combine a coarse pattern in the interior with an induced magnetic field ∇ × A almost aligned with B ext at the surface, see Figure 1 for a sketch. Experimentally, this is manifested by complex patterns observed at the surface of the sample [Pro07,PGPP05,PHC08,PH09]. This phenomenon of domain branching occurs also in other areas of materials science, as for example ferromagnetic materials, where the magnetization pattern is constrained to oscillate between two opposite vectors [Lif44,Hub67], and in shape-memory alloys, where the strain can oscillate between finitely many values, corresponding to the different martensitic variants.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…This permits to combine a coarse pattern in the interior with an induced magnetic field ∇ × A almost aligned with B ext at the surface, see Figure 1 for a sketch. Experimentally, this is manifested by complex patterns observed at the surface of the sample [Pro07,PGPP05,PHC08,PH09]. This phenomenon of domain branching occurs also in other areas of materials science, as for example ferromagnetic materials, where the magnetization pattern is constrained to oscillate between two opposite vectors [Lif44,Hub67], and in shape-memory alloys, where the strain can oscillate between finitely many values, corresponding to the different martensitic variants.…”
Section: Introductionmentioning
confidence: 92%
“…This permits to combine a coarse pattern in the interior with an induced magnetic field ∇ × A almost aligned with B ext at the surface, see Figure 1 for a sketch. Experimentally, this is manifested by complex patterns observed at the surface of the sample [Pro07, PGPP05,PHC08,PH09]. This phenomenon of domain branching ext κ 2/3 T 1/3 L 2 , which is the optimal scaling if b ext ≥ κ 5/7 /T 2/7 .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. For further background we refer the reader to several books and reviews.…”
Section: Introductionmentioning
confidence: 99%
“…The domain structure of type-I superconductors was found to depend on the magnetic history. In series of papers Prozorov et al [47][48][49] have shown that based on the way of how the final B − T point is reached, different types of domain structures might be realized. In order to check the influence of the magnetic history on the TF-µSR response, several B − T points approached by different measurement schemes were examined.…”
Section: Magnetic History Effectsmentioning
confidence: 99%